2021
DOI: 10.1016/j.jcot.2021.101515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 pandemic on arthroplasty services and early experience after resuming surgeries at a ‘non Covid’ center

Abstract: Background: The aim of this study is to assess the impact of Covid-19 crisis on hip and knee joint replacement surgeries at a high volume tertiary care hospital in the Indian National Capital Region and to evaluate the early experience of resumption of arthroplasty services. Methods: Institutional records of the arthroplasty cases, operated between 1st March to 31 August of 2019 (Group A, pre-Covid) and 2020 (Group B, pandemic year) were compared retrospectively over numerous parameters including the complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…April 2020 represented the greatest drop in monthly surgical volumes of primary TKA and THA. This is in line with studies of the early impact of COVID-19 in the US and abroad [ 5 , 15 , 16 ]. Revision procedures showed a more modest decline with just over half of revision knee and hip cases being lost, suggesting prioritization of higher acuity procedures.…”
Section: Discussionsupporting
confidence: 89%
“…April 2020 represented the greatest drop in monthly surgical volumes of primary TKA and THA. This is in line with studies of the early impact of COVID-19 in the US and abroad [ 5 , 15 , 16 ]. Revision procedures showed a more modest decline with just over half of revision knee and hip cases being lost, suggesting prioritization of higher acuity procedures.…”
Section: Discussionsupporting
confidence: 89%
“…4,10 An 82.53% drop in arthroplasty was observed in an Indian study. 11 An Austrian study observed an 18.6% decrease in primary arthroplasty and 15.8% in revision arthroplasty. 12 In Romania, a decrease of up to 55.47% for primary and 69.14% for revision arthroplasty was reported.…”
Section: Discussionmentioning
confidence: 99%
“…This study is comparable to previous studies. 9,11,15 However, one study saw a rise in the readmission rate, which may correlate with the decreased recovery time. 11 Some studies, however, reported a contrasting result with an increase in the average length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations